Vertex operators and soliton solutions of affine Toda model with U(2) symmetry - Cabrera-Carnero, I; Gomes, J. F.; Sotkov, G. M.; Zimerman, A. H. (Iop Publishing Ltd, 2004)
The symmetry structure of the non-Abelian affine Toda model based on the coset SL(3)/SL(2) circle times U(1) is studied. It is shown that the model possess non-Abelian Noether symmetry closing into a q-deformed SL(2) circle times U(1) algebra. Specific two-vertex soliton solutions are constructed.